2017
DOI: 10.1371/journal.pone.0179267
|View full text |Cite
|
Sign up to set email alerts
|

Reduced total serum bilirubin levels are associated with ulcerative colitis

Abstract: Chronic inflammation associated with inflammatory bowel disease (IBD) results in increased oxidative stress that damages the colonic microenvironment. Low levels of serum bilirubin, an endogenous antioxidant, have been associated with increased risk for Crohn’s disease (CD). Therefore, the aim of this study was to examine whether total serum bilirubin levels are associated with ulcerative colitis (UC). We identified a retrospective case-control population (n = 6,649) from a single tertiary care center, Penn St… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 29 publications
3
25
0
Order By: Relevance
“…These variables were the basic laboratory exponents (WBC RBC, MCV, neutrophils, lymphocytes, monocytes, eosinophils, basophils, glucose, bilirubin, AspAT, ALAT, amylase, PT, INR, fibrinogen, urea, creatinine, sodium, potassium, CRP) and collected additional information from the basic patient's interview (age, gender, smoking, occurrence of blood in the stool, palpable tumor within the abdominal cavity). There are no concrete studies on these attributes in IBD [12][13][14][15][16][17][18][19][20][21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These variables were the basic laboratory exponents (WBC RBC, MCV, neutrophils, lymphocytes, monocytes, eosinophils, basophils, glucose, bilirubin, AspAT, ALAT, amylase, PT, INR, fibrinogen, urea, creatinine, sodium, potassium, CRP) and collected additional information from the basic patient's interview (age, gender, smoking, occurrence of blood in the stool, palpable tumor within the abdominal cavity). There are no concrete studies on these attributes in IBD [12][13][14][15][16][17][18][19][20][21].…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between abnormal hepatic biochemical parameters (AspAT and ALAT) and IBD is not fully understood. Approximately 29% of patients with IBD have abnormal results of liver function tests [18]. Increased serum amylase is often observed in patients with IBD without any clinical signs of pancreatitis [12].…”
Section: Data Collectionmentioning
confidence: 99%
“…Leníček et al [ 28 ] performed an exploratory case-control study that included 90 cases of CD and 229 healthy controls, and they concluded that CD was associated with obviously lower levels of sTB, which resulted in an increased level of oxidative stress. Moreover, the study conducted by Kathleen et al [ 8 ] evaluated the relationship between sTB and UC at 2 medical centers and found a reduction of sTB in UC patients compared with healthy individuals. However, in contrast to our study, Sen et al [ 29 ] suggest that sTB levels were raised in CD patients compared to controls, and patients with active stage disease exhibited higher levels of sTB compared to patients in a remission phase.…”
Section: Discussionmentioning
confidence: 99%
“…Serum total bilirubin (sTB) possesses a protective effect against metabolic syndrome and diabetes [ 4 ]. Quite a few studies have demonstrated the correlation between reduced levels of sTB with several diseases such as cardiovascular disease [ 5 , 6 ], rheumatoid arthritis [ 7 ], and inflammatory bowel disease (IBD) [ 8 ]. In a retrospective case-control study, Schieffer et al [ 8 ] found that patients with UC exhibited lower levels of sTB compared with healthy individuals.…”
Section: Introductionmentioning
confidence: 99%
“…Lenicek et al [74] calculated that per 1 mmol/L reduction in total bilirubin, one of the main contributors to TAS like described earlier, a risk for CD manifestation increases by 13%. In turn, Schieffer et al [76] evaluated that for the lowest quartile of total bilirubin the likelihood of CD manifestation was 1.9-fold higher in a learning set of patients and, even more elevated, 3.6-fold higher, in a validation cohort.…”
Section: Diagnostic Markers In CDmentioning
confidence: 99%